2012
DOI: 10.1186/1745-6215-13-232
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of traditional Chinese medicine, Shen-Mai San, in cancer patients undergoing chemotherapy or radiotherapy: study protocol for a randomized, double-blind, placebo-controlled trial

Abstract: BackgroundCancer is one of the major health issues worldwide. An increasing number of cancer patients are offered treatment with surgery, chemotherapy and radiotherapy. Traditional Chinese medicine (TCM) is one of the most common complementary therapies offered to cancer patients in Taiwan. We designed a randomized, double-blind, placebo-controlled clinical trial to evaluate the efficacy of TCM in patients with cancer.Methods/designIn this study, inclusion criteria are postoperative patients with histologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 25 publications
0
25
0
1
Order By: Relevance
“…The results showed that some TCMs such as TJ-41 used alone or in combination with chemotherapy or supportive care showed significant relief in cancer-related fatigue and improved quality of life compared to chemotherapy or supportive care based on single trials. In addition, a randomized, double-blind, placebo-controlled clinical trial was conducted to evaluate the efficacy of Shen-maisan (a famous Traditional Chinese herbal formulation composed of processed Ginseng, Liriope spicata, and Schizandrae fructus) in patients with cancer who were undergoing chemotherapy or radiotherapy (95). Shenmai-san was found to be effective for treating cancerrelated fatigue and had anti-fatigue activity.…”
Section: Fatiguementioning
confidence: 99%
“…The results showed that some TCMs such as TJ-41 used alone or in combination with chemotherapy or supportive care showed significant relief in cancer-related fatigue and improved quality of life compared to chemotherapy or supportive care based on single trials. In addition, a randomized, double-blind, placebo-controlled clinical trial was conducted to evaluate the efficacy of Shen-maisan (a famous Traditional Chinese herbal formulation composed of processed Ginseng, Liriope spicata, and Schizandrae fructus) in patients with cancer who were undergoing chemotherapy or radiotherapy (95). Shenmai-san was found to be effective for treating cancerrelated fatigue and had anti-fatigue activity.…”
Section: Fatiguementioning
confidence: 99%
“…Currently, SMI is a famous Chinese patent-protected injection that has been widely applied in clinical practice for treating shock with qi and yin deficiency, coronary heart disease, viral myocarditis and tumors [4] . Various pharmacodynamic studies have demonstrated that SMI is effective in cancer interventions as an adjunct agent to chemotherapy [4,8,16] . Shenmai was found to be effective in treating cancer-related fatigue and the side effects induced by chemotherapy or radiotherapy [16] , which can be explained by the synergistic effect of Shenmai for qi and yin.…”
Section: Discussionmentioning
confidence: 99%
“…Various pharmacodynamic studies have demonstrated that SMI is effective in cancer interventions as an adjunct agent to chemotherapy [4,8,16] . Shenmai was found to be effective in treating cancer-related fatigue and the side effects induced by chemotherapy or radiotherapy [16] , which can be explained by the synergistic effect of Shenmai for qi and yin. However, there is a lack of direct evidence to confirm the chemosensitization function of SMI or its underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…17 More significant synergistic effects on symptom control have been observed with all the ingredients combined. 18 TCM methods for managing chronic fatigue have been widely adopted for the treatment of cancer and other conditions in China and elsewhere. [19][20][21][22][23][24] In oncology care, the TCM method most often used in China is a mixture of herbal compounds and decoction.…”
Section: Discussionmentioning
confidence: 99%